Nom d’un chien, nom d’humain ? Ces noms d’animaux qu’on utilise pour parler de nous - Daniel Elmiger (Glad!)
This column explores the intersection between gender and the vocabulary used to describe animals and human beings, highlighting the associated metaphors and stereotypes. Using a database of common nouns referring to humans, nearly 500 terms also refer to animals, illustrating a rich semantic exchange between the two domains. Overall, the negative characteristics attributed to animals – and then to ourselves – are far more frequent than the positive properties.